Elementary statistics Step by step approach - Bluman, Allan G. (McGraw-Hill, 2012)
Suitable for introductory statistics courses with a basic algebra prerequisite, this book explains concepts intuitively and teaches problem solving through worked examples and step-by-step instructions. It focuses on Excel, MINITAB, and the TI-83 Plus and TI-84 Plus graphing calculators; computing technologies commonly used in such courses.